'Unpractical' objects. The concept of the King's Gifts in the Old Norse World - Katona, Csete (2014)
According to Actor-Network-Theory, an object can have agency in social relations just as much as humans (Latour, 2005). In Old Norse literature, heroic weapons are well-known examples of objects being actors in the formulation of the plot (Torfing, 2012). However, they can have an important influence not solely for their mighty abilities as tools of violence, but sometimes for an unexpected reason as well: their social importance. During this survey, I shed light on the fact that objects are not always handled according to their primary role and function as social symbols rather than actual tools of violence. This fact is illustrated through the examination of two swords called ‘Konungsnautr’ in Laxdaela saga, which are not involved in violent actions, unlike other named weapons in the same saga. Other instances from Egil’s saga, Gunnlaug saga or the saga of Harald Fair-Hair will strengthen the idea that Laxdaela saga is not the only example where symbolic artefacts are actors. An axe used against oxen, swords which do not kill or a cloak which is never worn all testify that “unpractically” handled objects have unique significance in Old Norse world. As we are dealing with objects, it is essential to be aware of the physical nature of these artefacts, thus the literary sources will be investigated alongside archaeological evidence (Eldjárn, 2000; Lund, 2014). This interdisciplinary research aims to develop our understanding about how were objects handled and opens up the possibility that by following actors we can better perceive the function of material culture in Viking societies. MSc/MA Történelem